Usabilidade, percepção estética e força de preensão manual: influência no design ergonômico de instrumentos manuais : um estudo com tesouras de poda - Campos, Lívia Flávia de Albuquerque [UNESP] (2014)
Ergonomics has an important rule in ensuring the usability of manual interfaces. Studies have addressed the ability of the musculoskeletal system and focused investigations in relation User x Technology at the level of the physical interactions. However, other interactions occur in sensory processes, which are responsible for promoting feelings of comfort, wellness and user identification with the product. This interactions has not been contemplated in the analysis of usability and includes the aesthetics shape or overall appearance. The aim of this study was to conduct a usability evaluation with simulated activities, which addressed the collection goals (band strengh) and subject data (perception of confort, discomfort and aesthetics) with Brazilian adults of different genders, age groups and two cities in Brazil, located in the Southeast and in the Northeast - Bauru-SP and São Luís-MA, respectively - in order to check if the aesthetic features of pruning shears have interaction with the perception of confort and discomfort use and, therefore, the perceived usability of these products, in addition to understand the influence of other variables which affect the carrying out of activities of use. This research has experimental basis. We evaluated 300 individuals distributed in two Brazilian cities, 150 subjects equally distributed in the ranges 18-29 years (25 and 25); 30-55 years (25 and 25); above 55 (25 and 25). The methods and techniques applied were based on meeting the criteria and biomedical ethics and recommendations. Data analysis was based on descriptive statistics and included the application of tests to verify the different statistically significant. The result indicate that for the pruning shears investigated, aesthetic perception influenced the perception of confort. The perception of comfort in turn is part of the perceived usability, included in the aspects of product satisfaction. The usability was also influenced...